Pengembangan Strategi Penjualan Melon Hidroponik melalui Direct Selling dan Pemanfaatan Media Sosial WhatsApp di PT ABN - Lucky Safitri; Uding Sastrawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
PT ABN is a company engaged in the cultivation and marketing of hydroponic melons using a greenhouse system. Increasing business competition has encouraged the company to implement effective sales strategies to improve market absorption and sales volume. This study aims to identify the company's internal and external factors, formulate appropriate sales strategies, and analyze sales performance before and after the implementation of direct selling and WhatsApp social media. The research employed descriptive and SWOT analyses supported by the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Internal-External (IE) matrices, as well as financial analysis using the RevenueCost Ratio (R/C Ratio). The results indicate that PT ABN is positioned in Cell I of the IE Matrix (grow and build), suggesting that market penetration and market development are the most appropriate strategies. These strategies can be implemented through the optimization of direct selling and the utilization of WhatsApp as a marketing medium. The financial analysis further shows that the hydroponic melon sales business is feasible and profitable.